Bactericidal Effect of Selected Antidiarrhoeal Medicinal Plants on Intracellular Heat-Stable Enterotoxin-Producing Escherichia coli - Birdi, Tannaz J. (Medknow Publications & Media Pvt Ltd, 2014)
Diarrhoeal diseases due to enterotoxigenic Escherichia coli continue to be a cause of global concern. Medicinal plants have been gaining popularity as promising antidiarrhoeal agents. In the present study, four antidiarrhoeal plants, viz. Aegle marmelos, Cyperus rotundus, Psidium guajava and Zingiber officinale were screened against a heat-stable toxin-producing enterotoxigenic E. coli strain. Decoctions of these plants were studied for their effect on intracellular killing of the bacterial strain using murine monocytic cell line, J774. [(3)H] thymidine release assay was used to evaluate the apoptotic/necrotic effect. All plants at concentrations <1% enhanced intracellular killing of the bacteria by J774 cells. However, at higher concentrations, the decoctions induced apoptosis in J774 cells. The study demonstrates that these plants could control diarrhoea caused by heat-stable toxin-producing enterotoxigenic E. coli through their immunomodulatory effect.